Power in Nature, Human Relations and Myth: Abduction and Rape in Ovid’s Landscape - Álvarez Espinoza, Nazira (2025)
The article develops an approach to Ovid’s Metamorphoses based on the study of landscape, the power of nature, human experience, and myth. It explores three specific lines of analysis through a mythic-symbolic interpretation in relation to nature, the mythical landscape, and the human relationships involved in abduction/rape narratives. Regarding the treatment of landscape, the study draws on the proposals of Guettel (2000), Berenstein (2011), and Behm (2020). Concerning gender dynamics, power, and the punitive nature of violence against the female body, it employs the approaches of Deschard (2009), Beek (2015), Block (2014), and Maturano (2017). Through the examination of various artistic and literary representations of the natural world, the work addresses the transformative power of nature and the theme of violence in mythical accounts of abductions and rapes as found in the poem. These narratives in the Metamorphoses reveal the lasting impact of Ovid’s landscape imagery on literature and art.